POLA KONSUMSI DAGING SAPI OLEH RUMAH TANGGA DI BANDAR LAMPUNG - Joni Parulian; Dyah Aring Hepiana Lestari; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The study aimed to know the pattern of beef consumption, factors that affected the demand of beef, and the elasticity of the demand of beef. The research was conducted in the city of BandarLampung on purpose, based on the class of  underprivilage households to privilage type III+, namely the upper class at Kemiling Permai Village of Kemiling Subdistrict, the middle class at Labuhan Ratu Village of Kedaton Subdistrict and the lower clas  at Pesawahan Village of Southern Teluk Betung Subdistrict. The sample in the study was 54 house wives. The data was collected from October-November 2013. The data was analyzed by qualitative analysis, multiple linear regression and analysis of the elasticity of demand.  The results showed as follows. The greatest amount of beef demand in the period of July–September 2013 was 0.5-3kg per 3 month, pieces of beef that was being the most widely consumed was chuck as much as 43.61kg per 3 month, frequency of beef consumption as much as 1-3 times in the period of July to September 2013, and a total of 76.64% of households chose the traditional market to buy beef.  Factors affected on beef demand by households in the city of BandarLampung were chicken prices, level of education, income and place of purchase. The cross elasticity between broiler chicken and domestic chickens was positive, it meant that beef was substitution stuff; and income elasticity of the demand of beef worth positive; so that beef was normal stuff. Key words: beef, consumption patterns, demand, elasticity, household